Lead absorption abilities of Bougainvillea (Bougainvillea spectabilis Willd.) and money plant (Epipremnum aureus G. S. Bunting) in lead-based paint coated compartments - Baron, Elsa May D. (Journal of Engineering, Environment and Agriculture Research, 2018)
Lead has multiple detrimental effects in developing children and pregnant women. It can cause behavioral problems and decrease in IQ among children while complications may occur among pregnant women. This research is focused on two plants, Epipremnum aureus (money plant) and Bougainvillea spectabilis (bougainvillea), and their ability to sequester lead from air released by lead-based paint. The age of the plants (young or mature) and the type of plants were the factors used in the study. Each plant was placed inside a wooden compartment for seven days, where the interior surfaces coated with lead-based paint. For baseline reading, one gram of leaves was collected from each plant before each was placed inside the painted compartment. Leaf samples were collected after the plants were placed inside the painted wooden compartment. The leaf samples were then subjected under atomic absorption spectroscopy to determine the amount of lead present. Results revealed that both Epipremnum aureum (money plant) and Bougainvillea spectabilis (bougainvillea) are capable of absorbing lead released in air from the lead-based paint coated compartments with differences at 2.4 ppm and 14 ppm; respectively. Statistical analysis showed that there were no significant differences on the lead absorption abilities of Bougainvillea spectabilis and Epipremnum aureum based on age (P=0.44). However, there was a significant difference in their capacity to absorb lead released in air based on the type of plant (P=0.009).